Generation of Induced Pluripotent Stem (iPS) Cells by Nuclear Reprogramming - Dilip Dey; Gregory R. D. Evans (Stem Cells International)
During embryonic development pluripotency is progressively lost irreversibly by cell division, differentiation, migration and organ formation. Terminally differentiated cells do not generate other kinds of cells. Pluripotent stem cells are a great source of varying cell types that are used for tissue regeneration or repair of damaged tissue. The pluripotent stem cells can be derived from inner cell mass of blastocyte but its application is limited due to ethical concerns. The recent discovery of iPS with defined reprogramming factors has initiated a flurry of works on stem cell in various laboratories. The pluripotent cells can be derived from various differentiated adult cells as well as from adult stem cells by nuclear reprogramming, somatic cell nuclear transfer etc. In this review article, different aspects of nuclear reprogramming are discussed.